In Search of New Drugs: Elucidating the Activity of Structurally Similar Potential Antibiotics Using Molecular Modelling - Natalina Makieieva; Teobald Kupka; Piotr Lodowski; Radosław Balwierz; Katarzyna Kasperkiewicz; Adam Byrski; Roksolana Konechna; Vira Lubenets (Molecules)
The global problem of antibiotic resistance leads to the necessity for drug improvement and discovery. Natural and synthetic sulfur-containing compounds have been known as antibiotics for many years. In the current study, we demonstrated an antibacterial activity of three new thiosulfonates: S-ethyl 4-aminobenzene-1-sulfonothioate (1), S-methyl 4-acetamidobenzene-1-sulfonothioate (2), and S-ethyl 4-acetamidobenzene-1-sulfonothioate (3). Their activities were studied on two model Gram-positive and Gram-negative bacteria strains: Staphylococcus aureus ATTC 6538P and Escherichia coli ATTC 8739, respectively. According to the literature data, we proposed a general mechanism of 1−3 biochemical actions. To analyze its feasibility, theoretical studies using density functional theory (DFT) were performed. The obtained results demonstrate a direct correlation between some NBO parameters and the S-S bond energy of 1−3 with their activity against both studied bacterial strains. The obtained results could be helpful for future biomedical studies on the analyzed compounds and promote the further design of new S-containing antibiotics.